(3LOhd GdejQGKs - (3eLghds
(3ChdgG (B:s
(3GdWHbI GdChdi ef GdfSH (B.. (3Cj GdKdKGf ef ZjQ JSejI (B.. (3eMLhHI HGdENhI Yf GdRGFO Ydi GdSOS aNeSI CSOGS efg (B..(3ef GdLOhd GdbWYI GdChdi CH, Ce , GHf, HfJ , GHf GdGHf , GHf GdHfJ , HfJ GdGHf (B...s
(3BNQgG (B:s
.. (3aEfg dG jfJbd Edi CHhj GdRhLjf hfMhgeG hdgPG dG jHGY hdG jhgH hceG jQK Gdehdi YJjbg eY abO GdfSH dg cPdc jQK ChdGO YJjbI eY abO GdbQGHI dge adh JYOO ehdi GdCH hGdCe (B.. (3ef eYJb GdCe Edi eYJb GdCH efgs
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3abg GdePGgH GdCNQis